Comparative transcriptomic and metabolomic analyses reveal differences in flavonoid biosynthesis between PCNA and PCA persimmon fruit - Wang, Yiru; Suo, Yujing; Han, Weijuan; Li, Huawei; Wang, Zhenxu; Diao, Songfeng; Sun, Peng; Fu, Jianmin (Frontiers in Plant Science, 2023)
The fruit of the persimmon (Diospyros kaki.) has high economic and nutritional value and is rich in flavonoids. Flavonoids are essential secondary metabolisms in plants. The association between persimmon astringency and changes in the proanthocyanidins (a flavonoid subclass) content is well-known. However, information on the relationships between different astringency types and other flavonoid subclasses and biosynthetic genes is more limited. In this study, an initial correlation analysis between total flavonoids and fruit astringency type, and KEGG analysis of metabolites showed that flavonoid-related pathways were linked to differences between mature pollination-constant non-astringent (PCNA) varieties (‘Jiro’ and ‘Yohou’) and pollination-constant astringent (PCA) fruit varieties (‘Zhongshi5’ and ‘Huojing’). Based on these findings, variations in the expression of genes and metabolites associated with flavonoid biosynthesis were investigated between typical PCNA (‘Jiro’) and PCA (‘Huojing’) persimmons during fruit development. The flavonoid concentration in ‘Huojing’ fruit was significantly higher than that of ‘Jiro’ fruit, especially, in levels of proanthocyanin precursor epicatechin and anthocyanin cyanidin derivatives. Combined WGCNA and KEGG analyses showed that genes such as PAL, C4H, CHI, CHS, F3H, F3'5'H, FLS, DFR, ANR, ANS, and UF3GT in the phenylpropanoid and flavonoid biosynthesis pathways may be significant factors impacting the proanthocyanin precursor and anthocyanin contents. Moreover, interactions between the R2R3MYB (evm.TU.contig7272.598) and WD40 (evm.TU.contig3208.5) transcription factors were found to be associated with the above structural genes. These findings provide essential information on flavonoid biosynthesis and its regulation in the persimmon and lay a foundation for further investigation into how astringency types affect flavor components in PCNA and PCA persimmons.